Different Types of Resistant Starch Elicit Different Glucose Reponses in Humans - Haub, Mark D.; Hubach, Kelcie L.; Al-tamimi, Enas K.; Ornelas, Sammy; Seib, Paul A. (My University, 2010)
The purpose of this study was to determine whether different types of resistant starch (RS) elicited different glycemic responses. Eleven healthy subjects consumed solutions containing 30 g of either dextrose (DEX), resistant starch type 2 (RS2), or cross-linked resistant wheat starch type 4 (RS4XL) on three separate occasions, which were assigned randomly. Finger stick blood samples were collected before and over the following two hours and measured for glucose. The incremental area under the curve (iAUC) for the glucose response was calculated for all trials. The two types of resistant starch significantly (P < .05) decreased iAUC compared withDEX.The response with RS4XL was significantly decreased compared with the RS2 trial. These data demonstrate that different types of resistant starch elicit significantly different glycemic responses.
Keywords: Dietary fiber; Obesity; Diabetes; Metabolic syndrome; Food; Functional fiber